Review of Law Number 11 of 2020 on Job Creation: Constitutionality Test Based on Constitutional Court Decision Number 91/PUU-XVIII/2020 - Burhanuddin, Ahmad; Priyana, Yana (West Science Law and Human Rights, 2025)
This study conducts a normative legal analysis of Law Number 11 of 2020 on Job Creation (commonly referred to as the Omnibus Law), focusing on its constitutionality as assessed in Constitutional Court Decision Number 91/PUU-XVIII/2020. The research examines the legal and procedural foundations of the law's formation and evaluates whether it adhered to the standards set by the 1945 Constitution of the Republic of Indonesia. The Constitutional Court declared the law "conditionally unconstitutional," citing procedural violations such as insufficient public participation, lack of transparency, and post-ratification changes. This paper discusses the legal reasoning behind the Court’s decision, the legislative implications of using the omnibus method, and the broader impact on Indonesia's legal and democratic processes. The findings emphasize the importance of constitutional compliance, legislative discipline, and meaningful public involvement in lawmaking to ensure legal certainty and democratic accountability